AN ISLAMIC SPIRIT FOR BUSINESS ETHICS AND LEGAL FRAMEWORK OF FINTECH PEER TO PEER LENDING: Why Does Indonesia Need It? - Aditya Prastian Supriyadi (Jurisdictie: Jurnal Hukum dan Syariah, 2022)
The growth of Fintech Peer-to-Peer (P2P) lending in Indonesia is one of the supports for national economic development. The positive growth of this financial sector is not supported by proportional rules, resulting in the practices of business ethics violation which is detrimental to society. To overcome these problems, the spirit of Islam can be the basis for determining ethical and business measures into a better legal framework for Fintech P2P Lending. This article applies a normative legal research method using a conceptual approach and legislation relevant to the theme of the study. The research results indicate that Fintech P2P Lending in Indonesia needs to be regulated in a qualified legal framework because the existing rules have not been able to solve unethical actions of businessmen. The business concept in Islam also accommodates ethical issues that must be applied in business activities as a harmless commerce spirit. This Islamic spirit can be used as a source of material law in determining a clear legal framework to uphold Fintech P2P Lending business ethics so as not to harm the Indonesian people.Pertumbuhan fintech peer-to-peer (P2P) lending di Indonesia merupakan salah satu penunjang pembangunan ekonomi nasional. Pertumbuhan positif sektor keuangan ini tidak diikuti dengan aturan yang proporsional sehingga menimbulkan praktik-praktik yang melanggar etika bisnis dan sangat merugikan masyarakat. Untuk mengatasi permasalahan tersebut, semangat Islam dapat menjadi landasan untuk menentukan langkah-langkah etis dan bisnis ke dalam kerangka hukum fintech P2P lending yang lebih baik. Artikel ini menggunakan metode penelitian hukum normatif dengan menggunakan pendekatan konseptual dan peraturan perundang-undangan yang relevan dengan tema penelitian. Hasil penelitian dalam artikel ini menunjukkan bahwa fintech P2P Lending di Indonesia perlu diatur dalam kerangka hukum yang mumpuni karena aturan yang ada belum mampu mengatasi tindakan tidak etis dari para pelaku bisnis. Konsep bisnis dalam Islam juga mengakomodir persoalan etika yang harus diterapkan dalam kegiatan bisnis sebagai spirit perdagangan yang tidak merugikan. Semangat keislaman ini dapat dijadikan sebagai sumber hukum materil dalam menentukan kerangka hukum yang jelas untuk menegakkan etika bisnis fintech P2P lending agar tidak merugikan masyarakat Indonesia.